Measuring central bank independence in selected transition countries and the disinflation process - Sandra Dvorsky (Bank of Finland, Institute for Economies in Transition (BOFIT), 2000)
The paper measures the degree of legal and actual central bank independence (CBI) in five Central and Eastern European transition economies striving for EU accession, namely the Czech Republic, Hungary, Poland, Slovakia and Slovenia (CEEC-5).The degree of legal CBI is measured by applying the two most widely used indices, the Cukierman and the Grilli-Masciandaro-Tabellini (GMT) indices. Moreover, the turnover rate of central bank governors is used as a proxy to measure actual CBI.The paper gives an interpretation of computed results, comparing the findings with those of other authors and earlier calculations.Furthermore, the indices on legal and actual CBI themselves are critically reviewed, in particular against the background of the Maastricht Treaty requirements, which in practice constitute the driving force for any amendment of central bank laws in the CEEC-5.Moreover, the role of CBI in bringing down inflation in the CEEC-5 at different stages of transition is briefly discussed.The paper concludes that the overall degree of legal CBI is comparatively high in all countries examined, while the measured turnover rates of governors do not seem to fully reflect the degree of actual CBI in the CEEC-5. Looking at the role of CBI in the disinflation process at different stages of transition, the main causes for inflation seem to have been beyond the direct control of the central bank.A high degree of CBI, together with a reasonable mix of fiscal and monetary policies as well as structural reforms, will be necessary for the CEEC-5 to meet all requirements for joining the EU and, in a more distant future, for adopting the euro.
URN:NBN:fi:bof-201408072116
Keywords: 330; transition; central bank independence; disinflation